CONCEPTUALIZING TEACHERS AUTONOMY IN LANGUAGE CLASSROOMS - Ummi Rasyidah (JEE (Journal of English Education), 2018)
The focus of this paper is on learner autonomy (henceforth, LA) in language classroom setting. LA is an engagement in a process of reflective practice in learning process. In what follows, I will first discuss concisely the concept of LA; next I will briefly discuss the work of possible differences among attributes affecting LA; finally, I will elaborate LA for language classroom, and will suggest how LA might be conceptualized according to LA principles. In the language classroom, LA is usually associated either with students or teachers. Moreover, LA as it stands for, generally considered as encouraging students to become more autonomous. Following Nasri, Dastjerdy, Rasekh and Amirian (2015), however, I suggest that gender, background, and experience as a valuable feature contribution to promote LA.